Multi-sulfonated ligands on gold nanoparticles as virucidal antiviral for Dengue virus - Zacheo, Antonella; Hodek, Jan; Witt, Dariusz; Mangiatordi, Giuseppe Felice; Ong, Quy K; Kocabiyik, Ozgun; Depalo, Nicoletta; Fanizza, Elisabetta; Laquintana, Valentino; Denora, Nunzio; Migoni, Danilo; Barski, Piotr; et al. (Scientific reports, 2020)
Dengue virus (DENV) causes 390 million infections per year. Infections can be asymptomatic or range from mild fever to severe haemorrhagic fever and shock syndrome. Currently, no effective antivirals or safe universal vaccine is available. In the present work we tested different gold nanoparticles (AuNP) coated with ligands ω-terminated with sugars bearing multiple sulfonate groups. We aimed to identify compounds with antiviral properties due to irreversible (virucidal) rather than reversible (virustatic) inhibition. The ligands varied in length, in number of sulfonated groups as well as their spatial orientation induced by the sugar head groups. We identified two candidates, a glucose- and a lactose-based ligand showing a low EC50 (effective concentration that inhibit 50% of the viral activity) for DENV-2 inhibition, moderate toxicity and a virucidal effect in hepatocytes with titre reduction of Median Tissue Culture Infectious Dose log10TCID50 2.5 and 3.1. Molecular docking simulations complemented the experimental findings suggesting a molecular rationale behind the binding between sulfonated head groups and DENV-2 envelope protein.
Keywords: virus dengue; Cercopithecus aethiops; Antiviral Agents; buněčné linie; lidé; Cell Line, Tumor; hepatocyty; buňky Hep G2; Cell Line; Dengue Virus; Hep G2 Cells; Molecular Docking Simulation; simulace molekulového dockingu; zlato; Chlorocebus aethiops; Humans; Hepatocytes; Vero buňky; kovové nanočástice; Metal Nanoparticles; Vero Cells; Gold; antivirové látky; dengue; Dengue; zvířata; Animals; nádorové buněčné linie; ligandy; Ligands